2006
DOI: 10.1016/j.jtcvs.2005.11.046
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Coapsys annuloplasty and internal reduction mitral annuloplasty in the randomized treatment of functional ischemic mitral regurgitation: Impact on the left ventricle

Abstract: Coapsys and reduction annuloplasty techniques both acutely reduce functional mitral regurgitation and annular dimension. The Coapsys device provided significantly greater left ventricular reshaping than did reduction annuloplasty. Further evaluation will assess the long-term valvular function and ventricular geometric stability associated with both techniques.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0
3

Year Published

2008
2008
2015
2015

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(28 citation statements)
references
References 17 publications
1
24
0
3
Order By: Relevance
“…Surgical experience suggests that a septal-lateral annular reduction of at least 8 mm is typically required for a successful repair in a straightforward case. 28,40 Multiple cases in this series have acutely demonstrated corrections of this magnitude ( Figure 3). However, the aggregate sustained reduction of the septallateral dimension of the mitral annulus ( Figure 6) has been less than the typical surgical correction.…”
Section: Evidence For Effectmentioning
confidence: 63%
See 1 more Smart Citation
“…Surgical experience suggests that a septal-lateral annular reduction of at least 8 mm is typically required for a successful repair in a straightforward case. 28,40 Multiple cases in this series have acutely demonstrated corrections of this magnitude ( Figure 3). However, the aggregate sustained reduction of the septallateral dimension of the mitral annulus ( Figure 6) has been less than the typical surgical correction.…”
Section: Evidence For Effectmentioning
confidence: 63%
“…[22][23][24] Current efforts include approaches to directly clip 25 the mitral leaflets or modify the mitral annulus via the coronary sinus 26,27 and various other novel techniques. 28 Preliminary data in both animal models and initial, temporary human studies have demonstrated the potential of the PTMA device (Viacor Inc, Wilmington, Mass) and the method to reduce the mitral annular septallateral dimension and limit MR. 29,30 This report describes initial results and procedure revisions in an intention-toimplant feasibility study.…”
mentioning
confidence: 99%
“…70 Another device utilizes a beating heart implantation of a circu lar band with inflatable chambers at the base of the left ventricle. 71 Other percutaneous techniques consist of a direct beating heart chordae implantation using a trans apical approach to treat prolapse or ruptured chordae tendinae in selected patients with degenerative MR. 72 Transcatheter mitral valve replacement is another inno vative approach. 63 Echocardiographic assessment of the dynamic changes in MR is crucial to guide these proce dures and monitor the effects of device implantation on mitral valve target lesions.…”
Section: Percutaneous Mitral Annuloplastymentioning
confidence: 99%
“…Grossi и соавт. [50] сравнивали результаты рестрик-тивной аннулопластики и имплантации Coapsys device. Оба метода эффективно уменьшали диаметр митрального отверстия и степень ишемической МР.…”
Section: применение эпикардиального ограничивающего желудочкового приunclassified